1986
DOI: 10.1021/ac00122a009
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric determination of platinum from aqueous solutions and from urine

Abstract: I t is shown that platinum can be determlned from aqueous solutions o f clsdiamminedicMotopiatinum( I I ) (cisplatin) or of hexachioropiathic acid by differential pulse voltammetry after deposnbn onto a rotating glassy carbon electrode. For cisplatln, deposltlon Is carried out at -0.5 V In 0.15 M NaCi. For hexachloroplatkdc acld best results are obtalned at -0.2 V In 0.1 Y NaHSO,/O.l M Na$04 buffer. The subsequent analysis step is performed In 0.05 M H,SO, after application of a controlled potentlal program to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This may cause loss of activity of some enzymes, which is a disadvantage of the present method. However, some platinum complexes such as cisplatin [cis-diaminedichloroplatinum (II)] have been shown to be platinized at a neutral pH (20). By selecting an appropriate platinum complex, intact immobilization of enzyme molecules may be easily carried out at moderate pH by the present electrochemical microfabrication techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause loss of activity of some enzymes, which is a disadvantage of the present method. However, some platinum complexes such as cisplatin [cis-diaminedichloroplatinum (II)] have been shown to be platinized at a neutral pH (20). By selecting an appropriate platinum complex, intact immobilization of enzyme molecules may be easily carried out at moderate pH by the present electrochemical microfabrication techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[404] DPV 100.0 mM KCl, pH 7.0 LOD ¼ 370.0 pM [405] (continued) PtEs electrolysis in the chlorine ions-containing solution while being placed in the Escherichia coli growing medium. Basic cisplatin redox reactions were also harvested electrochemically during its plating over the GCE followed by its oxidation (analytical step) [395] or direct reduction at the Hg-based electrodes. [396] Indirect sensing of cisplatin was realized on HMDE modified with metallothionein (MT) by monitoring an increase in the reduction peak of Pt 2þ -MT protein complex [397] and on CPE with electrodeposited AgNPs, [398] with the latter procedure providing a lower LOD of 3.2 nM.…”
Section: Other Antineoplastic Agentsmentioning
confidence: 99%
“…Electrochemical methods based on accumulation of cisplatin at a glassy carbon [137] and a hanging mercury drop electrode [138] were des-…”
Section: Polarographymentioning
confidence: 99%
“…Both studies found a good detectability for cisplatin in water, but in urine the detector response disappeared, probably by competition for the active sites on the electrode surface by organic surfactants and by depositing metal ions [138]. Therefore, platinum detection was only possible by indirect assay [138] or by complexation to hexachloroplatinic acid, deposition of this product at -0.2 V (versus satured calomel electrode) and detection at +0.9 V [137].…”
Section: (3) 1992mentioning
confidence: 99%
See 1 more Smart Citation